2007
DOI: 10.1111/j.1540-8167.2007.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment Mapping of a Concealed Nodoventricular Accessory Pathway in a Man with Complete Heart Block and Tachycardia‐Induced Cardiomyopathy

Abstract: Entrainment Mapping of a Concealed NV AP. True nodoventricular (NV) accessory connections, as originally described by Mahaim, are rare entities, with the majority of previously reported cases now recognized as being due to decremental atriofascicular pathways. Here, we present a patient with incessant narrow and wide QRS complex tachycardia occurring in the setting of prior complete heart block. Entrainment mapping proved useful in diagnosing orthodromic reentry utilizing a concealed right septal NV pathway. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…43 In this case, atrial extrastimuli fail to induce advancement of the following preexcited QRS complex, the next retrograde His bundle deflection where apparent, and the subsequent atrial deflection without changing the retrograde atrial activation sequence, as may happen in the presence of a macroreentrant loop ( Figure 6). Although no extensive series have been published, application of entrainment criteria (SA-VA and PPI-TCL) from the apex 44 or the apex and the base for differential entrainment 45 is theoretically appealing and has been proposed to distinguish between antidromic AVRT and AVNRT with a bystander fiber.…”
Section: Electrophysiology Studymentioning
confidence: 99%
“…43 In this case, atrial extrastimuli fail to induce advancement of the following preexcited QRS complex, the next retrograde His bundle deflection where apparent, and the subsequent atrial deflection without changing the retrograde atrial activation sequence, as may happen in the presence of a macroreentrant loop ( Figure 6). Although no extensive series have been published, application of entrainment criteria (SA-VA and PPI-TCL) from the apex 44 or the apex and the base for differential entrainment 45 is theoretically appealing and has been proposed to distinguish between antidromic AVRT and AVNRT with a bystander fiber.…”
Section: Electrophysiology Studymentioning
confidence: 99%
“…4 Limited data suggest that manifest fusion during right ventricular entrainment of ORT using a nodal AP is specific to a nodoventricular fiber. 20 Because the circuit for NFRT is contained within the specialized conduction system, ventricular fusion cannot occur with paced complexes that penetrate the excitable gap and entrain tachycardia (analogous to AVNRT). Although this is true when collision between antidromic and orthodromic wavefronts occurs in the AV node or His bundle, it is not when the collision point is in the right bundle distal to the bifurcation of the His bundle and proximal to the take-off of the NF AP.…”
Section: Nodal Pathwaysmentioning
confidence: 99%
“…Based on the evidence accruing from cases reported over the last decades, such arrhythmias are known to be less common than those produced by concealed nodofascicular pathways (Figure , lower panel; 17, 26, and 31). In this regard, an incessant tachycardia mediated by either a nodoventricular or a nodofascicular pathway, with ensuing arrhythmic‐induced cardiomyopathy, was reported by Quinn et al, with a series of three such patients reported more recently …”
Section: Introductionmentioning
confidence: 82%
“…It is now 38 years, nonetheless, since Gallagher et al were able to prove that an antegradely conducting nodoventricular pathway could be involved in an anatomical circuit producing an antidromic tachycardia. Subsequent to this report, multiple investigators have shown that concealed pathways, either originating from the atrioventricular node or the ventricular components of the axis, can function as the retrograde limb of orthodromic reciprocating tachycardias, as well as acting as “bystander” pathways during atypical atrioventricular nodal reentrant tachycardia . On occasion, the pathways can also act as bystanders in the antegrade limb of an atrioventricular nodal reentry tachycardia (AVNRT) .…”
Section: Introductionmentioning
confidence: 99%